Chemical Composition and Antibacterial Activities of Rhizome Extract from Curcuma aromatica Salisb. - Siramon, Pornpun; Waeonukul, Rattiya (YRU Journal of Science and Technology, 2021)
In this study, the bioactive compound was extracted from Curcuma aromatica rhizome. The chemical composition of bioactive compound extract was determined by Liquid Chromatography - Mass Spectrometry (LC-MS). Five compositions were identified and were classified into 2 groups namely, (1) Nonvolatile Curcuminoids: Bisdemethoxycurcumin, Demethoxycurcumin, Curcumin and (2) Volatile compounds: Furanodienone and Turmerone. Furthermore, the crude extract was analyzed to evaluate their antibacterial activity against 3 human pathogenic strains: Staphylococcus aureus DMST 8840, Staphylococcus epidermidis DMST 15505 and Methicillin-resistant Staphylococcus aureus (MRSA) DMST 20651. The results revealed that C. aromatica crude extract exhibited antibacterial activity against all tested bacterial strains with minimal inhibitory concentration (MIC) value of 25.60 mg/ml and minimal bactericidal concentration (MBC) values in the range of 25.60-51.20 mg/ml.